The analysis of phase, dispersion and group delay in InGaAsP/InP microring resonator - Amiri, I.S.; Alavi, S.E.; Supa'at, A.S.M.; Ali, J.; Ahmad, Harith (Penerbit UTM Press, 2016)
The Vernier operation with signal flow graph (SFG) is a graphical approach for analyzing the intricate photonic circuits mathematically and quick calculation of optical transfer function. Analysis of a cascaded microring resonators (CMRR) made of InGaAsP/InP semiconductor is presented using the signal flow graph (SFG) method which enables modelling the transfer function of the passive CMRR. These passive filters are mostly characterized by their frequency response. The theoretical calculations of the system is performed by the Vernier effects analysis. Two MRRs with radius of 100 μm which are vertically coupled together are used to generate resonant peaks. Here, the phase, dispersion and group delay of the generated signals are analyzed.